TEACHING VOCABULARY USING FLASHCARD - Supriatin, Titin; Rizkilillah, Venska Prajna (PROJECT (Professional Journal of English Education), 2018)
Vocabulary learning and teaching has been considered as one of the most important mechanisms of any educational program since early. Teachers have been using many techniques to help the learners to develop their knowledge of vocabularies in quality and quantity. There are many media in teaching vocabulary, one of them is by using flashcard. Flashcard is one of media which can help the teacher to teaching English easily. Flash cards in teaching vocabulary are very simple visual aids and the teacher can make the students more active during the teaching learning process. The study was conducted to find out the effect of flashcard on the vocabulary of the sixth graders of elementary school. This study employed a pre-experimental research design with one group pretest and posttest. An the research method used in this research is quantitative research with experimental research method. The subject consisted of 29 students of the sixth grader class of SDN Rengasdengklok Selatan 2 in the academic year of 2017/2018. Data collection techniques used in this study is a test. The procedures of collecting data are pretest, treatment and posttest. The data were analyzed using the SPSS 21.0. Based on the analysis, the mean score in pre-test was 66.21 improve to 79.55 in post-test. The result of t-test showed that significant 2-tailed was lower than 0.05 (0.000 < 0.05). It can be said that H0 is rejected, it means that there is effect of flashcard to the vocabulary of the sixth graders in SDN Rengasdengklok Selatan 2